Critical social policy and the capability approach - Otto, Hans-Uwe; Ziegler, Holger (Barbara Budrich Publishers, 2014)
The (European) welfare state, as well as the political space of "the social," is currently being reorganized in a fundamental way. This has major implications for any attempt to contribute to a more just or even emancipatory way of shaping "the social." This book discusses what the Capabilities Approach may contribute to the attempt. Rather than assessing the philosophical foundation of this approach, the book critically discusses the potentials and pitfalls of analyzing social and labor-market policy and, in particular, social services from a capabilities perspective. --Provided by publisher